Effects on Proliferation and Differentiation of Human Umbilical Cord-Derived Mesenchymal Stem Cells Engineered to Express Neurotrophic Factors - Yi Wang; Youguo Ying; Xiaoyan Cui (Hindawi Limited, 2016)
Mesenchymal stem cells (MSCs) are multipotential cells with capability to form colonies in vitro and differentiate into distinctive end-stage cell types. Although MSCs secrete many cytokines, the efficacy can be improved through combination with neurotrophic factors (NTFs). Moreover, MSCs are excellent opportunities for local delivery of NTFs into injured tissues. The aim of this present study is to evaluate the effects of overexpressing NTFs on proliferation and differentiation of human umbilical cord-derived mesenchymal stem cells (HUMSCs). Overexpressing NTFs had no effect on cell proliferation. Overexpressing NT-3, BDNF, and NGF also had no significant effect on the differentiation of HUMSCs. Overexpressing NTFs all promoted the neurite outgrowth of embryonic chick E9 dorsal root ganglion (DRG). The gene expression profiles of the control and NT-3- and BDNF-modified HUMSCs were compared using RNA sequencing and biological processes and activities were revealed. This study provides novel information about the effects of overexpressing NTFs on HUMSCs and insight into the choice of optimal NTFs for combined cell and gene therapy.